(3TQM bUjOI GdfGHZI GdPHjGfi (B((3GdOGdjg (B)s - (3CHi GdMSf Ydj Hf CMeO Hf eMeO Hf Ydj eJhjg GdhGMOi GdfjSCHhQis; (3RjGO Hf eYGhjI Hf VHGH GdPHjGfqj GdZWaGfqj GdeVQj, CHh CeGeI (B((3GdnqfGHnZI GdoqPrHnjGfj(B)s ((3CHh GdYdG Hf CHj GdahGQS GdbWhi s)
(3ChdgG (B:s
(3jGOGQ ejg HGdYdjGA aGdSfO Cbhi aWGd YdjgG SGda GdCHO s
(3BNQgG (B:s
(3gPG GdPi PcQJ YRQi aEf de JfaYfi JMjQJ hde CgJO dhLg JeJ GdbUjOI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3Jfab ai ChdgG hBNQgG eY GdfSNI GdChdis
(3HGNJdGa ai HYV CdaGXgGs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs